PERTANGGUNG JAWABAN PIDANA TERHADAP PENYALAHGUNAAN DANA DESA UNTUK KEPENTINGAN PRIBADI YANG DILAKUKAN OLEH MANTAN KEPALA DESA LONTARDI KABUPATEN SERANG - Nyimas Ratih Zahnur Annisa; Neni Kusuma Dewi, Marito Yolanda Tampubolon, Septia Lestari (ADMIN: Jurnal Administrasi Negara, 2024)
The number of criminal acts of corruption continues to increase from year to year, especially losses to state finances and other cases that often occur. Corruption has spread to almost all elements of society, one of which is the village head whose object is village budget funds. The research method used is a normative juridical approach and an empirical approach. This research aims to determine the motives for corruption offenses committed by the former head of Lontar village, Serang Regency, as well as the criminal liability of perpetrators of corruption crimes committed by the former head of Lontar village, Serang Regency. The results of this research show that the motive for violations of corruption and misuse of village funds committed by the former head of Lontar village, Serang Regency was to create village activity plans aimed at obtaining budget support from the center for implementing these activities. However, in reality, this activity was not carried out and was only a fictitious activity so that the funds received were used for the perpetrator's personal interests. Not only that, it turned out that the perpetrator also did not provide honoraria or salaries to village staff and allowances to the BPD were also not paid. Then, the criminal responsibility for the criminal act of corruption and misuse of village funds committed by the former head of Lontar village, Serang Regency, the perpetrator was found guilty and sentenced to 6 years' imprisonment and a fine of idr. 250,000,000 subsidiary 3 months in prison. Then he was sentenced to pay compensation equal to the value of the state losses he had caused.